Indian agricultural development since independence - Dantwala, M.L. (New Delhi, 1986)
The Indian Society of Agricultural Economics initiated a proposal in 1981 to prepare a book on Indian agriculture and its development since Independence. Such a book is needed by students of agricultural econo mics and the general reader in order to get acquainted with the major developments that have taken place in Indian agriculture since then. The book makes a modest attempt to critically review the developments in Indian agriculture during the planning era and highlights major policy issues that have arisen in the process of plan implementation. It includes a collection of 21 essays dealing with various aspects of Indian agriculture and rural development. Being a collaborative effort, the credit goes entirely to the authors who have contributed to this book.
Keywords: Agricultural development project India